Continuous ambulatory peritoneal dialysis peritonitis guidelines – Consensus statement of peritoneal dialysis society of India - 2020 - Tarun K Jeloka (Wolters Kluwer Medknow Publications, 2021)
Continuous ambulatory peritoneal dialysis (CAPD) related peritonitis is a major cause of technique failure, morbidity, and mortality in patients on CAPD. Its prevention and management is key to success of CAPD program. Due to variability in practice, microbiological trends and sensitivity towards antibiotics, there is a need for customized guidelines for management of CAPD related peritonitis (CAPDRP) in India. With this need, Peritoneal Dialysis Society of India (PDSI) organized a structured meeting to discuss various aspects of management of CAPDRP and formulated a consensus agreement which will help in management of patients with CAPDRP.